COVID 19 in Pregnancy: Immunology Savior or Culprit - BRINDERJEET Kaur (Journal of Medical Biomedical and Applied Sciences, 2021)
Corona pandemic has been a nightmare for health care, from the point of view of transmission, pathogenesis, diagnosis and treatment, everything in doldrums. Pregnancy in itself encompasses altered physiology, immunity and often is characterized by unpredicted bodily responses. The short review is an attempt to summarize the knowledge gained so far in context with COVID 19 infection in pregnancy. The paper highlights gaps in our present understanding and emphasize on more research for understanding the double edged sword - immune system and its response to COVID 19 infection in pregnant woman.